Genetic diversity of the INPA germoplasm bank of camu-camu (Myrciaria dubia [H.B.K.] McVaugh) using microsatellites markers (EST-SSR) (2011)
The knowledge of genetic diversity in Amazonian species is of great importance for domestication and breeding purposes. A great difficulty with non-domesticated species such as “camu-camu” is the lack of information about their genetic variability. Due to the economic potential of camu-camu, a fruit with a high level of vitamin C production, the aim of this study was to estimate the genetic diversity using the molecular markers EST-SSR, to study the genetic variability of 139 accessions from 17 “camu-camu” materiales from different rivers in the Brazilian's Amazon region, preserved at the INPA (Instituto Nacional de Pesquisas da Amazônia Brasilera) Active Germoplasm Bank (BAG) of “camu-camu” in Manaus. Eight of the EST-SSR polimorfic loci used had 102 alleles detected with an average of 12.87 alleles per locus. The results show high levels of diversity for all loci with an average expected heterocygocity (He) of 0.797 and a total heterocygocity (Ht) value of 0.502. Populations had high inbreeding values, suggesting a heterocigotes deficiency as observed by the heterocigocity (Ho), perhaps as result of the great distance and isolation among populations, which limits gene flow and favors inbreeding. A high genetic differentiation value (FST) of 0.21, indicates high variability among populations. Measures based on the alleles frequency, showed a larger variability within populations (80.3%) than among populations (19.7%). Genetic distances between populations showed high differences within accessions coming from Rondonia (Jaru) and those from Amazonas (and Pirarucu Tarumã) and Roraima (Urubu). The dendogram made by the UPGMA method, showed two major groups and five subgroups related geographically. Results proved EST-SSR marker's utility in genetic diversity studies among BAG of camu-camu. These results will be useful in planning new collections, germplasm conservation and population variability analysis, as well as directional crossover using divergent genotypes; which will contribute to camu-camu breeding in Amazonian countries.